First successful laparoscopic pancreaticoduodenectomy in Bangladesh: Surgical procedure and operation outcome - Md Ismail Gazi; Mohammad Salauddin Mia; Mohammad Emrul Hasan Khan (Clinical Surgical Oncology)
In October 2023, the first laparoscopic pancreaticoduodenectomy (LPD) operation was successfully conducted in Bangladesh. This case study reported the surgical technique and outcomes of Bangladesh's first LPD procedure. The patient was a 55-year-old male patient with the diagnosis of periampullary carcinoma. He underwent a classical LPD lasting 360 ​min with a blood loss of 170 ​ml. Postoperatively, he experienced no major complications such as pancreatic fistula or bile leakage but developed atelectasis, which was managed effectively. His postoperative pain, assessed on a scale from 0 to 5, significantly reduced from day 3 (score 3) to day 7 (score 1). Histological examination confirmed adenocarcinoma at the ampullary site, with an R0 resection margin achieved. Sixteen lymph nodes were retrieved, none of which showed involvement. His hospital stay was 10 days, and he returned to work 14 days post-discharge. This operation marks a significant milestone in advancing surgical practices in Bangladesh. The successful completion of the first LPD in Bangladesh demonstrated the procedure's feasibility, safety, and potential benefits in a similar resource-limited setting.